ANALISIS KEKERASAN BAJA S45C HASIL HARDENING DENGAN VARIASI MEDIA PENDINGIN - Subagiyo Subagiyo; Asrori Asrori; Lisa Agustriyana (Universitas Lambung Mangkurat, 2018)
Steel has good mechanical properties compared with the other materials, that is strength, hardness, rigidity, etc. Specially the steel hardness can be increased by heat treatment (Hardening). The purpose of this research is to obtain information about hardness of S45C steel after hardening by variation of cooling media. This research were used Ø 25 mm x 10 mm S45C steel, Hardened by variation of cooling media and then they were tested by Rockwell Harness Test. The result showed that the hardness of S45C steel after hardening increased from about 15 HRC (before hardening) to 71.89 HRC (Brane quenching), 68.22 HRC (Water quenching), 64.67 HRC (Water + Soluble oil quenching) and 56.89 HRC (Oil quenching), but for the range were opposite to 3.84 HRC (Brane quenching), 4.24 HRC ( Water quenching), 4.22 HRC (Water + Soluble oil quenching) and 5.65 HRC (Oil quenching)